REALIZING UZBEK NATIONAL-CULTURAL WORDS IN THE WORK “BYGONE DAYS” BY ABDULLA KADIRIY - Yakhyaeva, Nigina Ibragim qizi (INTERNATIONAL CONFERENCES, 2022)
The article covers a broad range of culture-bound words, realia translation, the identification of the main types and difficulties of translation based on the material of literary works translated from Uzbek into English. There analyzed the national and historical realias and national features, problems of similarity and equivalency in translated artistic composition in the first novel in Uzbek language written by A.Kadiriy – “ByGone Days”